Design of a Control Approach to Assist the Performance of a Competitive Line Follower Robot - Amorim, Johann S. J. C. C.; Fernandes, Jefferson H. O.; Machado, Matheus S.; Canella, André L. C.; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2022: Anais do XIV Simpósio Brasileiro de Robótica e XIX Simpósio Latino Americano de Robótica, 2022)
This research describes the development of a control strategy to optimize a competitive line follower robot for standard races developed by a team of CEFET/RJ called WolfBotz. Therefore, all mathematical foundations and robot models, hardware, and electronics involved in the construction of the proposed prototype will be described, as well as the regulation used in the competitions in Brazil. A discussion regarding the calculation of the PID control parameters is also provided. From the results, it was possible to conclude that the angular PID control with the linear PID strategy provides good stability to the robot to perform the line tracking.